Critical analysis of methods for the measurement of volatile fatty acids. Issue 3 (1st February 2016) - Fernández, Rodrigo; Dinsdale, Richard M.; Guwy, Alan J.; Premier, Giuliano C.
ABSTRACT: Volatile fatty acids are formed during microbial fermentation of organic matter and are present in a wide range of matrices, i.e., wastewater, landfill leachates, human and animal fluids, food, and environmental systems. Therefore, their quantification and speciation is important in the analysis of such natural systems. The difference in nature and complexity of the matrices has resulted in the development and publication of a great number of procedures for volatile fatty acid determination. This review gives an overview of sample preparation, separation conditions, and suitable detectors for each separation technique with a comparison of the limits of detection and the linear dynamic ranges attainable.